Volume 069 Leadership Pipeline i den offentlige sektor - Dahl, Kristian; Søholm, Thorkil Molly (Academic Quarter | Akademisk kvarter, 2013)
The theory Leadership Pipeline has in the last approx. ten years come into widespread use as a descriptive framework for large international cooperations and the way they define, develop and measure their leaders at every levels (Kaiser, 2011). The theory describes the skills, priorities and work values needed for managers at different organizational level, and is often associated with Charan, Drotter and Noel (2001). But as the article shows the theory is based on a wide tradition in organizational theory and management theory. This article presents the results of a qualitative research project that examined whether the skills, priorities and work values described in the Leadership Pipeline theory at four generic management levels can be transferred to a Danish public sector context – or if modifications or even rejections has to be made in/to the theory. Through a series of qualitative focus group interviews with approx. 100 Danish government leaders from four levels of management levels we were working on these issues. The analysis of the data indicates that the theory must be supplemented by eight competences.